Exploring mechanisms of excess mortality with early fluid resuscitation: insights from the FEAST trial - Maitland, Kathryn; Kiguli,Sarah; Olupot-Olupot, Peter; Akech, Samuel O.; Opoka, Robert O.; Nyeko, Richard; Nteziyaremye, Julius (BMC medicine, 2013)
Early rapid fluid resuscitation (boluses) in African children with severe febrileillnesses increases the 48-hour mortality by 3.3% compared with controls (nobolus). We explored the effect of boluses on 48-hour all-cause mortality byclinical presentation at enrolment, hemodynamic changes over the first hour, andon different modes of death, according to terminal clinical events. We hypothesizethat boluses may cause excess deaths from neurological or respiratory eventsrelating to fluid overload.